A study of the collection management of the Sampaguita Pictures Film Archive - Alejandrino, Brinerdine G.; Buenrostro, Juan Jr. C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1997)
This case study was conducted to determine the collection management practices of the Sampaguita Pictures. It aimed to answer questions that asked whether there are other materials, aside from the 16-mm films and the 35-mm films, collected in the library. It also tackled on the present collection development practices of the Sampaguita Pictures Film Archive; on how they were able to get the films or copies of the films back after most of the films were lost and sold. The collection development practices of the Sampaguita Pictures Film Archive are affected by certain factors. The Sampaguita Pictures has a filmography used instead of catalogs for the films. Like most special libraries, the clients of the film archive are only the administration and the film archive staff of the Sampaguita Pictures Film Archive. There are existing policies on the management of the collection of the film archive, specifically for handling and treatment of films and for outside users. The Sampaguita Pictures Film Archive observe preservation techniques used for the restoration and preservation of the films. The film archive is funded by the Sampaguita Pictures Inc. and most of the income generated by it goes to the management of the collection. 35 percent of the fund is used for the acquisition of materials, 50 percent for the maintenance and preservation and 10-15 percent for the staff. Major improvement in the space allocated for the film archive is one of the targets of the Sampaguita Pictures Inc. Improvement in the preservation techniques and, of course, equipment is a must, thus, having a 24-hour air conditioning. The biggest dream to have the collection of films fully restored in either the United States or Australia, but most especially, more funds should be generated to make this goal feasible
Typescript.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Collection management (Libraries)--Philippines.; Sampaguita Pictures Film Archive